A review of high frequency emission in 2-150 kHz range - Tomina Thomas; Prawin Angel Michael (International Journal of Advances in Applied Sciences, 2020)
This paper reviews state-of part of discussion that concern about high frequency emission. Sometimes there may be emission in the range of high frequencies because of the fast improvement of energy saving equipments in our homes. Investigators and standardized organization given a very much importance to the disturbances of power quality that occur in the range middle of 2-150 kHz. Disturbances of these high frequencies are becoming an increasing concern in the industry, particularly due to the growth of distributed and embedded generation. Now days, a large number of researches are proceeding at a large number of places, yet information regarding supraharmonics remains confined.